Indirect positive health outcomes of COVID-19: a systematic review. (May 2023) - Gebeyehu, D.T.; East, L.; Wark, S.; Islam, M.S.
Abstract: Objectives: The aim of this study was to assess the frequency of indirect positive health outcomes as a result of the COVID-19 pandemic. Study design: This was a systematic review. Methods: Articles were identified from four online databases (Web of Science, Scopus, PubMed and Google Scholar) using predetermined search terms. After studies were systematically identified, the results were summarised narratively. The indirect positive health outcomes associated with the emergence of COVID-19 and measures taken for its prevention were categorised into four health dimensions (physical, mental, social and digital). Results: After initial screening, 44 articles were assessed for eligibility, and 33 were included in the final sample. Of the included studies, 72.73% noted a benefit from COVID-19 prevention measures in the physical health dimension. In addition, 12.12%, 9.09%, 3.03% and 3.03% of articles reported a positive impact in the digital, mental, social and combined digital and mental health dimensions, respectively. Conclusions: Despite the catastrophic health, socio-economic and political crises associated with the COVID-19 emergency, it has also resulted in some positive health outcomes. Reduced air pollutants, improved disease prevention practices, increased digital health delivery and improved mental and social health dimensions were reported during the pandemic. Integrated and collaborative activities for the persistence of these health benefits are recommended. Graphical abstract: Image 1